AN ALGORITHM FOR SETTING ENVIRONMENTAL QUALITY TARGETS ON THE EXAMPLE OF KOSTANAY REGION (Eurasian Journal of Ecology, 2024)
At the beginning of 2021, the new Environmental Code of the Republic of Kazakhstan came into force, aimed at gradually improving the quality of the environment. One of the requirements of the regulatory document is the establishment of environmental quality targets by each region. Kostanay region was one of the first in the republic to establish environmental quality targets under the new Rules that came into force in the middle of 2021. The rules for the quality targets development describe only the requirements for which components of the environment should be established, what should follow after setting environmental quality targets (meaning environmental protection measures), but the algorithm and sources of the information are not indicated in the rules. This work was carried out in Kostanay region in 2023, and this article describes not only the results obtained, but also the stages of the work, sources of information and conclusions obtained in the form of proposed quality indicators. The article describes the algorithm of the work carried out to establish quality targets for the Kostanay region.Keywords: environment, ecology, solid waste, greenhouse gases, maximum permissible concentrations, atmospheric air, water resources, land degradation and desertification.